Migración y fecundidad: Un análisis cuali-cuanti de cubanas residentes en Canadá - Michel López Barrios (2021)
This dissertation deals with the reproductive behavior of migrant women. Such behavior undergoes adaptation processes in different ways compared to that of women in the place of origin or destination, depending on whether they are first or later generation of migrants. The main theories that address the relationship between fertility and migration (selectivity, adaptation, socialization, and disruption) are interrelated, even though there are no conclusive results, which motivates further study. In this way, we seek to discover how the reproductive behavior of migrant women evolves, using information from Cuban women residing in Canada whose migration was basically for three reasons: i) Regulated labor opportunity (economic pathway); ii) Family reunification, and iii) Refuge. The available sources that address this objective are the 2016 Canadian demographic census and primary data collection. We used consequently, quantitative analysis complemented with qualitative analysis of in-depth interviews made to 15 Cuban women residing in the city of Montreal, Quebec, Canada. In addition to the traditional theoretical approaches of the relationship between these two variables, this dissertation outlines some of the proximate determinants of fertility such as union patterns, contraceptive use, and abortion, as well as the context of reproductive health and family planning in the destination. Quantitative results show us that Cuban refugee women have a higher relative risk of having had children than women of economic status and family reunification, suggesting a strategy of legitimizing permanent residence in Canada. These results corroborate what was found in the above descriptive analysis for Cuban refugee women: a higher total fertility rate and a less harmonious shape of the curve, suggesting the presence of disruption. Through the in-depth interviews, we were able to determine that the migration of Cuban women is mainly due to economic reasons and suggests the existence of a migratory culture. The use of contraceptive methods does not show marked differences among the groups studied, regardless of the level of schooling. The practice of abortion was widely accepted by the interviewees, some of whom had abortions both in Cuba and in Canada, which would corroborate the existence of an abortion culture. Factors such as the lack of support from close relatives, the employment conditions of both the woman and her partner were highlighted as the most important in the decision to have children among the women interviewed among all the profiles.